Dispositional of Goal Orientation in Soccer Player Performance on Different Position - Bisyri Husin Musawi Maliki, Ahmad; Razali Abdullah, Mohamad; Juahir, Hafizan; Nazarudin, Nuraini; Shuhada Razak, Hawa; Atikah, Nik (International Journal of Engineering and Technology, 2018)
This study investigates dispositional of goal orientation in player performance on different positions. Data were obtained from 223 participants in a research aged 13 to 17 years old in Malaysia. Data interpretation was carried out using cluster analysis (CA) and discriminant analysis (DA).Â Players completed the Task and Ego Orientation in Sport Questionnaire (TEOSQ) and physical fitness test (v sit-up, agility, speed 5m, 10 and 20m, sergeant jump, sit and reach). CA was applied on motivation orientation which divided group according to their homogenous and DA was use for psychology that determine differences on player performance in different soccer positions. CA projected three groups form known as HTHE, LTME and MTLE and DA successfully discriminate three groups on 13 independent variables with 79.82% (forward stepwise) with total of 67 potential players. Each dispositional groups of goal orientation tend to show specific characteristics, attribute of soccer performance and physiological capacity. Finding of this study show insight of motivational dispositional characteristic lead to discrepancies of soccer performance and characterize the suitable players on each position in soccer.Â Â